Numerical simulation and experiment for study on internal flow pattern of vortex pump. Issue 5 (31st July 2019) - Quan, Hui; Chai, Yi; Li, Rennian; Guo, Jianhui
Abstract : Purpose: The special structure of the vortex pump contributes to its complex internal flow pattern. A type of horizontal 150WX-200-20 vortex pump is taken as a research subject to deeply study the progression and distribution of flow pattern in its channel. To explain the mechanism of flow in this pump, numerical analysis of the whole flow and experiment have been conducted. Design/methodology/approach: The authors studied and analyzed the distribution and evolution of flow pattern under different flow, such as circulating-flow, through-flow and other forms. Finally, a model of flow pattern in the vortex pump has been built, which has more perfectly fit the reality. Findings: They are through-flow affected by circulating-flow, main and subsidiary circulating-flow, vortices between vanes and other vortices (or liquid impingement) in volute. Entering the pump, part of the flow stays in vanes and turn into vortices while the other goes into the front chamber. The flow that runs into the front chamber will be divided into two parts. One part will be collected by viscosity into a vortex rope when it passing through the interface between the impeller and the vaneless chamber, which closely relates to the circulating-flow, and the rest directly goes out of the field through the diffuser. Besides, a fraction of circulating-flow joins the through-flow when it goes through the section V and leaves the pump. Originality/value: The research results build a theoretical foundation for working out the flow mechanism of the vortex pump, improving its efficiency and optimizing its hydraulic design.